A new modeling and solution approach for the number partitioning problem. Issue 2 (25th July 2005) - Alidaee, Bahram; Glover, Fred; Kochenberger, Gary A.; Rego, Cesar
Abstract : The number partitioning problem has proven to be a challenging problem for both exact and heuristic solution methods. We present a new modeling and solution approach that consists of recasting the problem as an unconstrained quadratic binary program that can be solved by efficient metaheuristic methods. Our approach readily accommodates both the common two-subset partition case as well as the more general case of multiple subsets. Preliminary computational experience is presented illustrating the attractiveness of the method.